Sustainable soil stabilization using industrial waste ash: Enhancing expansive clay properties - Almuaythir, Sultan; Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Hoque, Md. Ikramul (Elsevier Ltd, 2024)
This study investigates the use of various industrial waste materials—silica fume (SF), cement kiln dust (CKD), calcium carbide residue (CCR), rice husk ash (RHA), and ground granulated blast furnace slag (GGBS)—as eco-friendly stabilizers for expansive clay soil (ECS). Laboratory tests were conducted to assess the impact of different proportions (3 %, 6 %, and 9 %) of these additives on the soil's physical, mechanical, and microstructural properties. Results indicated that the inclusion of industrial waste significantly improved the soil's behavior, with notable reductions in liquid limit (up to 37.66 %), plasticity index (up to 74.76 %), and swell potential. Additionally, unconfined compressive strength (UCS) and shear strength increased substantially, with UCS values rising from 114.64 kPa to 1582.91 kPa at 30 days of curing for 9 % GGBS. Microstructural analyses confirmed the formation of cementitious compounds, which enhanced soil particle bonding and durability. These findings suggest that industrial waste materials can serve as effective and sustainable alternatives to traditional soil stabilizers, offering both performance improvements and environmental benefits.